THE INFLUENCE OF LIFESTYLE, PRICE, AND PRODUCT QUALITY ON PURCHASE DECISIONS AT THRIFT SHOPS IN PADANG - Intan Christina Agtri Saragih; Ratni Prima Lita; Laura Amelia Triani (RADJA PUBLIKA, 2025)
Fashion has become one of the emerging industries in Indonesia with the increasing purchasing power of the society, social media exposure, and globalization, which drives the society to make it a means of self-expression and lifestyle manifestation. Amid fast-fashion trends, thrift fashion appears as an alternative for sustainable and affordable clothing consumption and grows popular, especially among young groups. Although the ban on the import of second-hand clothing has been imposed, the thrift shop phenomenon continues to grow in many different cities, including Padang. This research analyzes the influence of lifestyle, perceived price, and product quality on consumer purchase decisions at thrift shops in Padang. A quantitative approach with a cross-sectional design was invoked. Data were collected through an online-based questionnaire with a 1-5 Likert scale distributed to 320 respondents, who were selected using the purposive sampling technique. The respondent criterion was consumers who previously purchased thrift products. Data analysis was carried out using the Structural Equation Modeling (SEM) technique with SmartPLS version 4.0 software. Results demonstrated that lifestyle, price, and product quality significantly and positively affected purchase decisions at thrift shops, confirming that thrift fashion consumptions were impacted by not only economic considerations but also lifestyle preferences and perceived quality, particularly among young groups, who were considered the latest trend-sensitive.